1998
DOI: 10.1046/j.1365-2672.1998.00363.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth-inhibitory effects of Galla Rhois-derived tannins on intestinal bacteria

Abstract: The growth‐inhibitory activity of Galla Rhois‐derived materials towards 17 intestinal bacteria was evaluated using an impregnated paper disc method. The biologically active components of Galla Rhois were characterized as the tannins methyl gallate (MG) and gallic acid (GA) by spectral analysis. The growth responses varied with bacterial strain tested. In the test using 10 mg disc−1, MG and GA produced a clear inhibitory effect on harmful bacteria such as Clostridium perfringens, Cl. paraputrificum, Eubacterium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 0 publications
6
68
0
Order By: Relevance
“…S. thermophilus cells were more sensitive to low concentrations of catechin than gallic acid, due to high degree of hydroxylation in catechin molecules (Puupponen-Pimiä et al 2005), in addition to its higher antioxidant capacity (Duda-Chodak et al 2008), which increases its antimicrobial activity. Our data agreed with those of Ahn et al (1998), that growth of bifidobacteria and lactobacilli were not adversely affected by gallic acid compared to other polyphenols, but were inconsistent with a recent report by Landete et al (2007) where flavonols (including catechin) had lower or similar antibacterial activity to phenolic acids. Total phenolic consumption in presence of 0.8% gallic acid or 0.3% catechin were estimated to be 36 ± 3.2 and 17 ± 2.5%, respectively under similar growth conditions, and were lower than those estimated by other workers (Alberto et al 2001).…”
Section: Resultssupporting
confidence: 84%
“…S. thermophilus cells were more sensitive to low concentrations of catechin than gallic acid, due to high degree of hydroxylation in catechin molecules (Puupponen-Pimiä et al 2005), in addition to its higher antioxidant capacity (Duda-Chodak et al 2008), which increases its antimicrobial activity. Our data agreed with those of Ahn et al (1998), that growth of bifidobacteria and lactobacilli were not adversely affected by gallic acid compared to other polyphenols, but were inconsistent with a recent report by Landete et al (2007) where flavonols (including catechin) had lower or similar antibacterial activity to phenolic acids. Total phenolic consumption in presence of 0.8% gallic acid or 0.3% catechin were estimated to be 36 ± 3.2 and 17 ± 2.5%, respectively under similar growth conditions, and were lower than those estimated by other workers (Alberto et al 2001).…”
Section: Resultssupporting
confidence: 84%
“…Several authors have reported the antimicrobial effects of Galla Rhois extracts and Galla Rhois-derived tannins. (Ahn et al, 1994;Ahn et al, 1998;Bae et al, 1998). However, there are few reports of the effects of gallotannins on dental biofilms and oral pathogens.…”
mentioning
confidence: 94%
“…Galla Rhois has been used for the treatment of various diseases, including skin disease, diarrhea, dysentery, hemorrhage, and leucorrhea (Zhu, 1998) and it has been shown that Galla Rhois and its components possess various biological activities, including antibacterial (Ahn et al, 1998), antimetastatic/anti-invasion (Ata et al, 1996), and protective effect on liver cells from apoptosis and necrosis (Park et al, 2008). Further, recent studies have shown that Galla Rhois inhibits the production of inflammatory cytokines in mast cells and gallates inhibit cytokine-induced nuclear translocation of NF-kappa B and expression of leukocyte adhesion molecules in vascular endothelial cells (Murase et al, 1999).…”
Section: Introductionmentioning
confidence: 99%